The Clinical Presentation and Nutritional Management of an Infant With Neonatal Abstinence Syndrome. Issue 1 (January 2018) - Gottesman, Kimberly; Chang, Kaitlyn; Feldman, Alexander; Ziegler, Jane
Abstract : Neonatal abstinence syndrome (NAS) is a term used to describe postnatal withdrawal syndrome that occurs in infants as a result of fetal exposure to drugs. Signs of NAS include high-pitched cries, jitteriness, feeding difficulties, and low birth weight. If NAS is suspected, infant urine and/or meconium samples are sent for analysis. Management of NAS includes pharmacological treatment and nonpharmacological approaches. This case report highlights the management of an infant who presented with signs of NAS, had feeding difficulties and poor weight gain, was hospitalized for 6 months, and experienced delayed drug withdrawal.